Implementation of Guided Inquiry Learning Model In Improving Critical Thinking Abilities of Grade VI Students - Yohana Panjaitan; Natalina Purba; Jon Roi Tua Purba (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to Implement the Guided Inquiry Learning Model in Improving Critical Thinking Skills of Grade VI Students at UPTD Sd Negeri 125138 Pematangsiantar. This research is a qualitative research. Based on the results of research that has been done through observation, interviews, and documentation, it can be concluded that the implementation of the guided inquiry learning model in the subject of PPKn, especially on the material